ANALISIS PARTISIPASI MASYARAKAT DALAM PENGAWASAN DANA DESA DI DESA BARU SUNGAI DERAS - Kumeira, Badar (RC-INSTITUT, 2018)
This study aims to determine the increase of public participation in the Monitoring of Village Funds in the New Village of Deras River Air Hangat Timur District Kerinci District. The approach used in this research is qualitative. The informants in this study as many as 9 people. techniques and data collection tools in this study are interviews, observation, and documentation. Data collection tools in the form of a list of questions, pens, books / papers. Individual government analysis unit in Village Fund Supervision in New Village of Deras River Kecamatan Air Hangat Timur Kerinci District. The results showed that community participation in the Monitoring of Village Funds in the New Village of Sungai Deras, Kecamatan Air Hangat Timur, Kerinci Regency has been running optimally. In running the monitoring of village funds has been running well, but there is an increase in public participation associated with financing not just funds from the government but self-help communities.